Reversed link between central pacific ENSO and Greenland–Barents sea ice - Yuxin Xie; Anmin Duan; Chao Zhang; Chuangzhi He; Qi Mao; Bingxian Liu (npj Climate and Atmospheric Science)
Abstract Winter Arctic sea ice is a crucial climate indicator, declining at an accelerated rate compared to the past and playing a significant role in Arctic amplification over recent decades. The sea-ice concentration (SIC) in the Greenland–Barents Sea (GBS) shows considerable interannual variability, yet the link between this variability and the El Niño–Southern Oscillation (ENSO) remains uncertain. Here, we identify a reversed relationship between the autumn Central Pacific (CP)-type ENSO and the winter GBS SIC around the mid-1980s. Observational and model experiments demonstrate that, before the mid-1980s, CP ENSO triggered a double wave pattern propagating toward the Arctic, generating a positive geopotential height anomaly in the Arctic. Such an anomaly, along with a northerly anomaly, favored cold-air advection and intrusion into the GBS, resulting in an increased SIC. After the mid-1980s, however, CP ENSO only induced a single wave train towards the Arctic, favoring a positive geopotential height anomaly over Iceland. As a result, the southerly anomaly transported abundant moisture into the GBS and consequently reduced the SIC. The variation in wave patterns can largely be attributed to the sea surface temperature anomaly in the tropical Atlantic induced by CP ENSO. Our findings highlight the unstable connection between tropical and polar regions, which provides a basis for better understanding the mechanisms of Arctic sea-ice changes.